Psychiatry in Qatar - Mohammed Mohammed; Ibrahim Makki; Suhaila Ghuloum (BJPsych International, 2023)
The first article written about psychiatric services in Qatar was published in BJPsych International in 2006. Since then, the health system in Qatar has undergone significant transformation in the areas of service delivery, research and education. International accreditations are sought in all these fields to emphasise the standard achieved. In this article, we follow up on the mental health services currently available in Qatar, their strengths and the associated challenges.